Development and Utilisation of Physics Learning Management System for Learning Difficult Concepts in Senior Secondary School Physics – Methodological Insights - Amusa, Jamiu Oluwadamilare; Adekunle, Oladejo Ibrahim; Adekunle, Ayanwale Musa; Lukuman, Bello; Adeshina, Adewale; Akintoye, Hakeem; Apata, Funke; Adeyemo, Sunday; Owolabi, Tunde (Asian Journal of Assessment in Teaching and Learning, 2024)
While science educators were battling the challenge of difficulty in learning physics, the sudden outbreak of the COVID-19 pandemic and the consequent lockdown of schools, compounded the existing ugly situation. This paper explored the methodological insights to the development and usability of Physics Learning Management System (PLMS). The study adopted the type II developmental research design to develop a functional PLMS using some of the existing digital technologies. Multistage sampling procedure was adopted to select 27 secondary school physics teachers in the six south-western states of Nigeria. The selected teachers were trained on the rubrics of instructional video production, Learning Management System and Culturo-Techno Contextual Approach (CTCA) model to teaching physics for five weeks. The results obtained were 86 instructional videos on perceived difficult topics in physics which were used as the content of the PLMS. To establish the validity and usability of the PLMS, 298 physics students were randomly selected from six public secondary schools across six states in south-west Nigeria. Feedback from the students and other technical observations were used to improve the functionality and usability of the PLMS. We hypothesized that the outcome of this study will over time, in addition to other similar initiatives, enhance physics learning in Nigeria in response to the call of the new normal and 4th industrial revolution. In addition to the urgent call for facility upgrades in public schools to promote virtual learning, it is also recommended upskilling and further capacity building should be encouraged among science teachers.